The Neuroimaging Role of Modified Electroconvulsive Therapy in the Major Depressive Disorder: Effectiveness in First-Episode Antipsychotic-Naive Major Depressive Disorder Patients - Zhong, Yi; Li, Jianfeng; Li, Haitao; Li, Mingzhe; Lyu, Yanaohai; Cui, Minghu; Gao, Yujun (Depression and Anxiety, 2024)
Objectives. It is a high risk for adolescents with first-episode major depressive disorder (MDD) to commit suicide. However, few studies reported the effect of modified electroconvulsive therapy (MECT) in first-episode antipsychotic-naive MDD adolescents. Methods. The study explores the alternations of regional homogeneity of modified electroconvulsive therapy to treat the first-episode antipsychotic-naive major depressive disorder. 72 first-episode MDD patients were recruited from Tianyou Hospital Affiliated to Wuhan University of Science and Technology from October 2017 to May 2020, and 65 of 72 completed the trial. Results. Before MECT treatment, ReHo values of the bilateral cerebellum and left cuneus were higher, and ReHo value of left postcentral and supramarginal gyrus was lower in MDD patients compared to healthy subjects (HS). After treatment, the MDD patients have higher ReHo values of the right insula and postcentral gyrus, while left fusiform gyrus were lower than the pretreatment. Compared to the HS, the ReHo values of left lingual gyrus, right calcarine cortex, and right mid occipital thalamus were higher in the posttreatment. In the posttreatment, left calcarine cortex and right cerebrum were lower than in healthy subjects. Conclusions. The study confirmed that MECT improves psychotic symptoms in patients with first-episode antipsychotic-naive MDD. These results further contributed to a more tailored treatment approach to MDD from the pathophysiological and neuroimaging views.